Cytokine and nitric oxide production by rat microglia stimulated with lipopolysaccharides in vitro - Du Ze-Ying; Li Xiao-Yu (Acta Pharmacologica Sinica; Vol 19, No 3 (May 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the characterization of interleukin (IL)-1, IL-2, tumor necrosis factor-alpha (TNF-alpha), and nitric oxide (NO) production in microglia stimulated with lipopolysaccharides (LPS). METHODS: Primary cultured neonatal rat microglia were incubated with LPS (0-10 mg.L-1) for 0-72 h. The supernatants and lysates were collected. IL-1, IL-2, and TNF-alpha were assayed by mouse thymocyte proliferation, mouse spleen cell proliferation, and 1929 cytotoxity, respectively. NO was assayed by Griess reaction. RESULTS: Extracellular IL-1, TNF-alpha, and NO production reached peak levels at LPS 1 mg.L-1. Intracellular IL-1 production reached its peak level at LPS 100 micrograms.L-1. Intracellular TNF-alpha level was very low. IL-1, TNF-alpha, and NO activities were detected at 1, 4, and 8 h, after the cells were stimulated with LPS. IL-1 got to its peak value at 8 h, TNF-alpha, and NO reached the highest levels at 24 h. However, IL-2 activity was not detected after the microglia were stimulated with LPS 0-10 mg.L-1 during the incubation period. CONCLUSION: Rat microglia stimulated with LPS in vitro produced proinflammatory cytokines and NO.